Integrating the Principle of Due Process in Restorative Justice for Women in Conflict with the Law: Contemporary Solutions in the Criminal Justice System Reform in Indonesia - Lysa Angrayni, (Proceeding International Conference on Social Sciences, 2026)
This study discusses contemporary solutions to the possibility that the principle of due process of law can be integrated with restorative justice, especially for the settlement of cases involving women as one of the vulnerable groups to receive discriminatory treatment in Indonesia. Women facing the law often face common phenomena such as gender discrimination, social stigmatization, and procedural injustices in the criminal justice system, especially in cases of domestic violence, human trafficking, or narcotics offenses. According to data from Komnas Perempuan in 2023, it has been mapped that there is a phenomenon that reflects a trend of increasing cases of gender-based violence (GBV) by 15-25% in the 2019-2023 range, where restorative justice (RJ) as an alternative approach often collides with the principles of due process of law, such as the right to fair and non-discriminatory legal process. This study integrates RJ with due process to create contemporary solutions in criminal justice system reform that are in line with Sustainable Development Goals (SDGs) Number 5 (Gender Equality) and Number 16 (Peace, Justice and Strong Institutions), which emphasize access to inclusive justice for women. The research method is normative with analysis carried out through a normative juridical approach, including conceptual interpretation combined with empirical evaluation of the case study to identify implementation gaps. From this study, it is hoped that it can recommend the integration model of RJ with the principle of gender-sensitive due process of law and recommendations for reform policies on the criminal justice system in Indonesia are expected to strengthen Indonesia's commitment to the SDGs and contribute to a more humane and inclusive criminal law discourse towards women.